Evidence-Based Medicine - A Paradigm Ready To Be Challenged? How Scientific Evidence Shapes Our Understanding And Use Of Medicine - Schulte, Marie-Caroline (J.B. Metzler : Imprint: J.B. Metzler, 2020)
This open access book aims to clarify the term "evidence-based medicine" (EBM) from a philosophy of science perspective. The author, Marie-Caroline Schulte discusses the importance of evi-dence in medical research and practice with a focus on the ethical and methodological prob-lems of EBM. The claims that EBM can herald a new theory of epistemology and a Kuhnian paradigm will be refuted. The solution is to describe EBM as a necessary development in medicine to deal with the increasing amount of evidence and medical data without loosing the single patient out of sight. Contents The methodology of evidence-based research Informed consent and shared decision making in EBM (Evidence-based medicine) Knowledge does not equal evidence - what to do with what we have evidence for? Homeopathy - a case in point why EBM is so important - or "the plural of anecdote is not data." Target Groups Lecturers and students in the areas of medicine and philosophy of medicine Researchers in philosophy of medicine, medical doctors, ethicists, philosophers and medical activists The Author M.-C. Schulte has studied philosophy and history in the US and finished her MSc in philoso-phy and history of science at LSE. She did her PhD in philosophy of science, focus on medi-cine, at Hamburg University. She works freelance in an advisory capacity for NGOs working in the medical field and writes articles in her area of expertise.